2020
DOI: 10.3897/zookeys.994.56277
|View full text |Cite
|
Sign up to set email alerts
|

A new species of Pristimantis (Amphibia, Anura, Strabomantidae) from the Pui Pui Protected Forest (central Peru), with comments on Pristimantis albertus Duellman & Hedges, 2007

Abstract: We describe a new Pristimantis species from the eastern Andes, Región Junín, Peru following an integrative taxonomic approach. The description is based on three adult males (snout-vent length 25.7–28.8 mm) collected in two montane forests between 1615 and 1800 m a.s.l. in the Pui Pui Protected Forest and its close surroundings. The new species is mainly characterised by absence of tympanum, presence of inner tarsal fold, broad horizontal red band across iris, ventre mottled black and cream and ventral surfaces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…However, genetic and morphological evidence demonstrated that "P. calcarulatus" was a complex of three different species, each with a small distribution range. Similar results have been found within "P. orestes", "P. ornatissimus" (Guayasamin et al 2017;Urgiles et al 2019), and P. ventrimarmoratus (Moravec et al 2020). It is unclear if species of Andean Pristimantis with large distributions (> 10000 km 2 ) actually exist.…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…However, genetic and morphological evidence demonstrated that "P. calcarulatus" was a complex of three different species, each with a small distribution range. Similar results have been found within "P. orestes", "P. ornatissimus" (Guayasamin et al 2017;Urgiles et al 2019), and P. ventrimarmoratus (Moravec et al 2020). It is unclear if species of Andean Pristimantis with large distributions (> 10000 km 2 ) actually exist.…”
Section: Introductionsupporting
confidence: 72%
“…Guayasamin et al 2015;Páez and Ron 2019). Taxonomic problems in Pristimantis are still pervasive and are still far from being fully resolved (e.g., Páez and Ron 2019;Reyes-Puig et al 2019;Moravec et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, the accumulation curve of described species is far from reaching saturation. The number of new species of Pristimantis described in the Cordillera Oriental of central Peru has reached 34 species in the last two decades [6][7][8][9][10][11][12][13][14][15][16][17][18] and the amount of information of each described species is constantly improving [10,14,17]. However, most species are currently known from few specimens and localities (e.g., P. adiastolus Duellman and Hedges, 2007, P. aniptopalmatus, P. eurydactylus Hedges and Schlüter, 1992, P. boucephalus Lehr, Moravec, Cusi, and Gvoždík, 2017, P. minutulus Duellman and Hedges, 2007, and P. rhabdocnemus Duellman and Hedges, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Compared to other species of Pristimantis from the Cordillera Oriental of central Peru, the new species is most similar to the sympatric P. albertus. Both species were common at the type locality, are similar in size (SVL 12.9-15.6 mm in males and 17.6-19.3 mm in females of P. clarae versus 12.9-19.5 in males and 19.7-24.2 in females of P. albertus; Duellman and Lehr [2], Moravec, Lehr and Kodejs [17]), and share the presence of dorsolateral folds. Moreover, both species belong to the P. danae species group.…”
Section: Comparison With Other Speciesmentioning
confidence: 91%
See 1 more Smart Citation